CHATBOT AS AN ADAPTIVE BUSINESS COMMUNICATION STRATEGY IN FACING DIGITAL ECONOMIC DISRUPTION - Ahmad Rizqi Suryadi (UIN Sunan Gunung Djati Bandung, 2025)
This article evaluates the impact of chatbots as an adaptive business communication strategy in the face of digital economic disruption. Digital economic disruption requires companies to implement agile communication strategies so that services can continue to operate amidst unstable market conditions. Chatbots are artificial intelligence-based conversational agents that have efficient interfaces and are always available for use. This article analyzes the role of chatbots as an adaptive communication strategy in the context of digital economic disruption. Rapid technological developments force the business world to innovate in how to interact with customers, especially amid uncertainty and changes in market demand. Chatbots—automated systems that can simulate conversations—are increasingly used by companies to improve communication efficiency and maintain service sustainability. Through a literature-based analysis, this article examines how chatbot adoption can support organizational agility, customer service innovation, and communication responsiveness. In addition, this article also highlights the ethical and practical challenges in implementing chatbots. The findings suggest that integrating chatbot technology into business communication strategies offers a relevant and adaptive solution to the demands of a disruptive digital economy.